Quantitative outcomes of a One Health approach to study global health challenges - Falzon, Laura C.; Lechner, Isabel; Chantziaras, Ilias; Collineau, Lucie; Courcoul, Aurélie; Filippitzi, Maria-Eleni; Laukkanen-Ninios, Riikka; Peroz, Carole; Pinto Ferreira, Jorge; Postma, Merel; Prestmo, Pia G.; Phythian, Clare J.; et al. (Springer, 2018)
Having gained momentum in the last decade, the One Health initiative promotes a holistic approach to address complex global health issues. Before recommending its adoption to stakeholders, however, it is paramount to first compile quantitative evidence of the benefit of such an approach. The aim of this scoping review was to identify and summarize primary research that describes monetary and non-monetary outcomes following adoption of a One Health approach. An extensive literature search yielded a total of 42,167 references, of which 85 were included in the final analysis. The top two biotic health issues addressed in these studies were rabies and malaria; the top abiotic health issue was air pollution. Most studies described collaborations between human and animal (n = 42), or human and environmental disciplines (n = 41); commonly reported interventions included vector control and animal vaccination. Monetary outcomes were commonly expressed as cost–benefit or cost–utility ratios; non-monetary outcomes were described using disease frequency or disease burden measurements. The majority of the studies reported positive or partially positive outcomes. This paper illustrates the variety of health challenges that can be addressed using a One Health approach, and provides tangible quantitative measures that can be used to evaluate future implementations of the One Health approach.